A simplified finite element model for structural cable bending mechanism. (July 2016) - Yu, Yujie; Wang, Xiaoxiang; Chen, Zhihua
Abstract: A simplified finite element modeling method for structural cables on bending and wire sliding problems are proposed and formulated. The model is characterized by a beam-spring composition that uses helically arranged short-beam elements to simulate spiral wires, radially-placed rigid beams to replace wire sections and spring elements to capture contact extrusion and friction between adjacent wires. Winding and contacting patterns for semi-parallel wire cables and spiral strands are discussed and then used to formulate the model establishments. In semi-parallel wire cable, any selected wire section can be simplified as a seven-node set to represent the center wire and the surrounded six contact spots. While in spiral strand, wire section can be replaced by four rigid beams that connect the four contact points to wire center. Helical wire compression, sheath pinch effect and contact friction are all considered and calculated, and then bending simulations are conducted on large dimension cables with different end conditions, wire constructions and pretension levels. Simulation results are compared to the test data, and prove that the proposed model can well predict the bending behavior and the varying trend of flexural stiffness. Both cables all express a bilinear elastic–plastic like flexural strength–deflection response. Semi-parallel wire cable has sinusoidal deflection out of the bending plane, and the range of bending gradient is influenced by the cable end conditions. Galfan strand shows little unwinding and torsion effect due to the canceling out effect from alternative twisting between adjacent layers. The model can efficiently simulate long and large dimension cables in a short time, implying its promising applicability in cable studies. Highlights: A simplified beam-spring finite element model is proposed for cable bending and wire sliding problems. Wires are simulated by helically arranged beam elements and contact interactions are captured by spring elements. Different contacting patterns of semi-parallel wire cables and spiral strands are discussed. Contact extrusion and friction resistance variation during the bending process can be captured. Bending stiffness, deflection mode and wire force redistribution conditions are well predicted.